Effectiveness of Drinking Coconut Oil in Pregnant Women on Flexibility of Portions during Labor at PMB Sutjiati in 2022 - Sutjiati; Feva (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
The effectiveness of drinking coconut oil in pregnant women on the flexibility of the portion during labor. Traditionally, people still use coconut oil a lot during pregnancy with the aim of smooth delivery. This is said by an expert is just a myth because there is no research. The author is interested in conducting research with the aim of knowing the condition of the portion of pregnant women, both those who drink and those who do not drink coconut oil during labour. The research method uses a descriptive study approach and qualitative research methods include: In-depth interviews with informants. Conduct random surveys. research by doing vaginal taucher on respondents who gave birth. The results of vaginal taucher examination on 40 respondents who gave birth: 35 respondents (87.5%) drank coconut oil, 5 respondents (12.5%) did not drink. Of the 35 respondents who drank coconut oil, 34 respondents (97.1%) became flexible, 1 respondent (2.9%) was not flexible. Results: Third trimester pregnant women who drink coconut oil regularly, most of the portions become flexible during labor. We know that a flexible portion is easier to dilate, so that the first stage of labor becomes faster, minimizes fatigue, reduces the risk of post-partum bleeding. Reducing the risk to the baby. Conclusion: The author believes this can contribute to reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Suggestion: the writer hopes that there will be more comprehensive research.